2020
DOI: 10.1111/tpj.14624
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Q gene near‐isogenic lines reveals key molecular pathways for wheat domestication and improvement

Abstract: † These authors contributed equally to this work. SUMMARYThe wheat AP2-like transcription factor gene Q has played a major role in domestication by conferring the free-threshing character and pleiotropically affecting numerous other traits. However, little information is known regarding the molecular mechanisms associated with the regulation of these traits by Q, especially for the structural determination of threshability. Here, transcriptome analysis of immature spike tissues in three lines nearly isogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…The previous section’s findings that Q and TaLAX1 physically interact to oppositely regulate domestication traits indicates that they might share some common target genes. Coincidentally, reported transcriptome data showed that some lignin biosynthesis‐related genes, including genes related to KNOTTED ARABIDOPSIS THALIANA7 ( KNAT7 ) and PHENYLALANIEN AMMONIA‐LYASA ( PAL1 ), were differentially expressed between the Q and q alleles (Zhang et al ., 2020). In this context, we speculated that TaLAX1 might also regulate the transcription of these lignin biosynthesis‐related genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous section’s findings that Q and TaLAX1 physically interact to oppositely regulate domestication traits indicates that they might share some common target genes. Coincidentally, reported transcriptome data showed that some lignin biosynthesis‐related genes, including genes related to KNOTTED ARABIDOPSIS THALIANA7 ( KNAT7 ) and PHENYLALANIEN AMMONIA‐LYASA ( PAL1 ), were differentially expressed between the Q and q alleles (Zhang et al ., 2020). In this context, we speculated that TaLAX1 might also regulate the transcription of these lignin biosynthesis‐related genes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the findings that Q has transcriptional repression activity (Liu et al ., 2017b) and that the transcriptional expression of TaPAL1‐6B decreases in the Q allele (Zhang et al ., 2020), we further investigated the regulatory effect of Q on TaPAL1‐6B transcription. To this end, transient expression assays were performed in N .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tauschii [30][31][32] and 2E in Lophopyrum elongatum [33]. Zhang et al [34] demonstrated that Q governs threshability through extensive modification of wheat glumes including their structure, cell wall thickness and chemical composition. The glume color is an important taxonomic discriminator in wheat [35,36] and is associated with the crop's adaptability [37,38].…”
Section: Introductionmentioning
confidence: 99%